Gold-catalyzed dehydrazinative C(sp)-S coupling reactions of arylsulfonyl hydrazides with ethynylbenziodoxolones for accessing alkynyl sulfones - Shinde, Popat S.; Patil, Nitin T. (European Journal of Organic Chemistry, 2017)
A gold(III)-catalyzed dehydrazinative coupling reaction between arylsulfonyl hydrazides and ethynylbenziodoxolone reagents was realized for the synthesis of alkynyl sulfones. The scope and versatility of the reaction were demonstrated by the efficient synthesis of 23 derivatives with diverse structural features.

Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes - Akram, Manjur O.; Shinde, Popat S.; Chintawar, Chetan C.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2018)
Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes are described. This redox neutral strategy offers an efficient approach to diverse biaryls, vinyl arenes and arylacetylenes. Monitoring the reaction with NMR and ESI-MS provided strong evidence for the in situ formation of Ph3PAuIR (R = aryl, vinyl and alkynyl) species which is crucial for the activation of aryldiazonium salts.